Excess of biopower : A bio and necropolitical analysis of microplastic circulation - Girot, Eva (2025)
This paper revisits Foucault's formulation of the excess of biopower (1976), employed to discuss atomic power, in order to contemplate the news of microplastic circulation in the biosphere. We will examine from a bio and necropolitical perspective the implications of microplastic circulation. Firstly, plastic will be addressed as a paradigmatic material of 20th-century late capitalism, exploring how its decomposition turns into microplastics. We will then show how the extensive and intensive circulation of this material destabilizes the Foucauldian notions of security, milieu, and regulatory power. Finally, the toxicity of this material will be exposed, along with its connection to the phenomenon of endocrine disruption as a form of necropolitics.